2022
DOI: 10.1051/e3sconf/202234705003
|View full text |Cite
|
Sign up to set email alerts
|

Disaster response network analysis in rural Temerloh, Pahang communities during the Malaysia 2020-2021 flood

Abstract: Disaster risk reduction practices can be viewed as a collaborative environment managed by a diverse group of stakeholders including governments, private sectors and non-governmental organizations and research institutes as well as local communities. Insufficient collaboration and failure to coordinate across groups can lead to unsuccessful disaster recovery efforts. This study investigates the organizational roles and collaboration network among governmental and community organizations participating in Malaysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 11 publications
1
3
0
Order By: Relevance
“…They clearly indicated that the prevention and preparedness of the general public are rather low and that makes high damage to the properties and lives of the region. Similar research work can be found in Yang et al (2012), Arun et al (2020), and Lam and Chow (2022). Not only for flood events but also for health-related disasters with floods, the situation reports were successfully used.…”
Section: Related Work In Other Countriessupporting
confidence: 59%
“…They clearly indicated that the prevention and preparedness of the general public are rather low and that makes high damage to the properties and lives of the region. Similar research work can be found in Yang et al (2012), Arun et al (2020), and Lam and Chow (2022). Not only for flood events but also for health-related disasters with floods, the situation reports were successfully used.…”
Section: Related Work In Other Countriessupporting
confidence: 59%
“…Centrality measures were employed to identify the most central actors [66]. The significance of the stakeholders can be initially evaluated using the Weighted Degree Centrality parameter.…”
Section: Stakeholder Network Analysis (Sna)mentioning
confidence: 99%
“…In this study, the communication networks under SNA (refer to Figure 3) were developed using Gephi software, version 0.10.1 [66], which is a social network analysis open-source software. Before feeding the data into the software, an adjacency matrix was created in Microsoft Excel for all three post-flood management phases using binary units (1 = connection exists between two stakeholders; 0 = no connection between two stakeholders) [67] to identify the connection between the stakeholders.…”
mentioning
confidence: 99%
“…One node can be identified in relation to several descriptors, which makes it possible to demonstrate the themes around which the communities are grouped, as well as their classification. The richer in terms of data a community is, the more connections are there between its nodes (Mishra et al 2011;Lam and Chow 2022).…”
Section: Social Media Network Analysismentioning
confidence: 99%